Emerging Drug Modalities Redefining Small-Molecule Therapeutics: Antibody–Drug Conjugates, Protacs, and Molecular Glues (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The landscape of drug discovery is undergoing a profound transformation with the emergence of new therapeutic modalities that extend beyond traditional occupancy-driven pharmacology. Antibody–drug conjugates (ADCs), proteolysis-targeting chimeras (PROTACs), and molecular glues exemplify this shift, emphasizing linker engineering, controlled payload release, and proximity-induced biological effects rather than classical high-affinity inhibition. These modalities harness endogenous cellular systems—such as targeted delivery mechanisms and the ubiquitin–proteasome pathway—to achieve enhanced specificity and catalytic or event-driven pharmacology. This paper provides a comprehensive examination of these innovative platforms, discussing their mechanistic principles, design strategies, materials and methods commonly employed in their development, experimental outcomes from representative case studies, and broader implications for future therapeutic innovation. The findings suggest that proximity-based and targeted degradation approaches offer distinct advantages in addressing undruggable targets, overcoming resistance mechanisms, and improving therapeutic indices. However, challenges related to stability, pharmacokinetics, immunogenicity, and largescale manufacturing remain significant. Continued integration of chemical biology, structural modeling, and translational pharmacology will be essential to fully realize the potential of these transformative drug modalities.